Evaluation of ibuprofen prescriptions into a Psychiatric Hospital: regarding safety, indication, and dose. - Dantas, Carolina Rosario; Couto, Ricardo David; Soares, Denis de Melo (Revista de Ciências Médicas e Biológicas, 2020)
Introduction: non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen are widely used throughout the world. In the psychiatric hospital, where this study was conducted, drugs such as selective serotonin reuptake inhibitors (SSRI) and lithium are widely used and may interact with ibuprofen (IBU). The literature also shows that ibuprofen may lead to changes in the central nervous system, which may trigger the imbalance of psychiatric disorders. Objective: to evaluate whether both the frequency of use and the prescriptions of ibuprofen are in agreement with the information contained in the literature regarding safety, indication, and dose. Methodology: retrospective observational cross-sectional study to evaluate the use of ibuprofen on patients from a psychiatric hospital. The prescriptions were evaluated for a 10-month period. Results: of the total number of prescriptions, 43 contained ibuprofen 600 mg. Note that in most cases, the drug was being prescribed according to the literature. However, in some cases there were divergences in the literature regarding: i) safety – information about the absence or presence of ulcers (1; 2.3%), gastrointestinal events (0; 0%) and absence of dyspepsia, abdominal pain and discomfort gastrointestinal (11; 25.5%) – ii) and the dose, in which in 19 cases (44%) it was higher than recommended by the literature. In addition, in 2 prescriptions (4.7%), the concomitant use of IBU and SSRI was observed and in 5 (11.6%) of IBU and lithium. Conclusion: the use of this drug often escaped safety and dosage criteria concerning scientific literature.